Enhanced water splitting activity of M-doped Ta3N5 (M = Na, K, Rb, Cs) - Kado, Yuya; Lee, Chong-Yong; Lee, Kiyoung; Müller, Julian; Moll, Matthias; Spiecker, Erdmann; Schmuki, Patrik (Chemical Communications, 2012)
We use a highly aligned Ta2O5 nanochannel structure to fabricate alkali metal ion (Na, K, Rb or Cs) doped Ta3N5 via solution seeding and thermal conversion in NH3. Under optimized conditions the resulting doped structures show a strongly enhanced visible light water splitting performance in comparison to undoped Ta3N5.